Dlaczego List do Hebrajczyków przypomina o pragnieniach patriarchów? - Malina, Artur (Collectanea Theologica, 2019)
The Pontifical Biblical Commission’s document The Jewish People and their Sacred Scriptures in the Christian Bible calls attention to a threefold connection between the two parts of the Christian Bible: continuity, discontinuity and newness. The paper offers an analysis of a passage as an example of this relationship. The Epistle to the Hebrews (11:8-22) puts a particular emphasis on the desires of the patriarchs among other attitudes of the heroes of faith. They were looking for what was promised to them and desired by them: a city with solid foundations planned and built by God. Now those desires can be fulfilled: the everlasting life with God is offered to all who believe in Jesus Christ.